Effect of Traditional and Virtual Oral Hygiene Instruction to School Health Instructors on Plaque Index of Elementary Schoolchildren - Golshah, Amin; Salahshour, Mahya; Kiani , Maryam; Fatahi , Ali (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: This study compared the effect of traditional and virtual oral hygiene instruction to school health instructors on plaque index (PI) of elementary schoolchildren. METHODS AND MATERIALS: In this descriptive, analytical study, 66 elementary schools in Kermanshah city were selected by cluster sampling. The school health instructors first participated in a pretest and filled out a questionnaire. The O’Leary’s index of 339 elementary schoolchildren was measured at baseline. Next, the school health instructors received oral hygiene instructions in two groups (n = 33) of virtual instruction through an online course and traditional classroom setting. After 3 weeks, a post-test was held and school health instructors filled out the same questionnaire for the 2nd time. After 3 months, the PI of students was measured again. Data were analyzed using the Chi-square test, t-test, Mann–Whitney U-test, and ANOVA. RESULTS: Both instruction methods significantly enhanced the oral hygiene knowledge of instructors (p < 0.001) but virtual instruction was significantly more effective (p = 0.02). No significant association was noted between age, work experience of instructors, or their level of education with their knowledge level in the virtual group (p > 0.05). An inverse correlation was noted between age and work experience of instructors with their knowledge level in the traditional instruction group (p < 0.05). Both instruction methods caused significant improvement of PI of students (p < 0.001) but virtual instruction was more effective (p < 0.001). CONCLUSION: Correct oral hygiene instruction to school health instructors (preferably by virtual instruction) can reduce PI elementary schoolchildren.